Artificial Molecular Machine Immobilized Surfaces: A New Platform To Construct Functional Materials. Issue 12 (2nd February 2016) - Zhang, Qi; Qu, Da‐Hui
Abstract: Artificial molecular machines have received significant attention from chemists because of their unique ability to mimic the behaviors of biological systems. Artificial molecular machines can be easily modified with functional groups to construct new types of functional molecular switches. However, practical applications of artificial molecular machines are still challenging, because the working platform of artificial molecular machines is mostly in solution. Artificial molecular machine immobilized surfaces (AMMISs) are considered a promising platform to construct functional materials. Herein, we provide a minireview of some recent advances of functional AMMISs. The functions of AMMISs are highlighted and strategies for their construction are also discussed. Furthermore, a brief perspective of the development of artificial molecular machines towards functional materials is given. Abstract : A little AMMIS : Artificial molecular machines have received significant attention from chemists. However, their practical application is still challenging, because the working platform of artificial molecular machines is mostly in solution. Herein, some recent advances of functional artificial molecular machine immobilized surfaces (AMMISs) are reviewed. The functions of AMMISs are highlighted and strategies for their construction are also discussed.